A multinational, prospective, observational study to estimate complete skin clearance in patients with moderate‐to‐severe plaque PSOriasis treated with BIOlogics in a REAL world setting (PSO‐BIO‐REAL). (8th June 2020) - Seneschal, J.; Lacour, J.‐P.; Bewley, A.; Faurby, M.; Paul, C.; Pellacani, G.; De Simone, C.; Horne, L.; Sohrt, A.; Augustin, M.; Hammond, E.; Reich, K.
Abstract: Background: Anti‐tumour necrosis factor (TNF) and anti‐interleukin (IL)‐12/23 biologics revolutionized plaque psoriasis treatment by enabling ≥75% improvement in the Psoriasis Area and Severity Index (PASI 75) in clinical trials. Modern biologics are now reported to achieve PASI 100 (complete skin clearance) in clinical trials. However, real‐world evidence of skin clearance rates with biologics is limited. PSO‐BIO‐REAL was conducted to understand the real‐world burden of plaque psoriasis. Objective: The primary objective of this observational study was to estimate the proportion of patients who achieved complete skin clearance at 6 months. Secondary objectives included maintenance of response and evaluation of complete skin clearance at 12 months. Methods: PSO‐BIO‐REAL was a multinational, prospective, real‐world, non‐interventional study of skin clearance and patient‐reported outcomes (PROs) with biologics. A total of 846 patients from the United States (32%), France (28%), Italy (22%), the United Kingdom (11%) and Germany (8%) were enrolled and followed for one year. Eligible patients were aged ≥18 years with moderate‐to‐severe plaque psoriasis who had initiated a biologic for plaque psoriasis. Patients could be biologic‐naïve or switching biologics (biologic‐experienced). Assessments were made at baseline and at months 6 and 12. Results: At 6 and 12 months, 23% and 26% of patients achieved complete skin clearance, respectively. Prior to study entry, 60% were biologic‐naïve. The proportion of patients achieving complete skin clearance was lower among biologic‐experienced patients (20% at both months 6 and 12) compared with biologic‐naïve patients (25% at month 6, 30% at month 12). The rate of complete skin clearance decreased as the number of prior biologics and baseline comorbidities increased. Conclusion: Only one in four patients achieved complete skin clearance after 6 months of treatment with biologics. The study indicates there still is an unmet need for more efficacious biologics for patients with psoriasis.